2016
DOI: 10.1021/acs.analchem.6b00087
|View full text |Cite
|
Sign up to set email alerts
|

Organelle-Targeted H2S Probes Enable Visualization of the Subcellular Distribution of H2S Donors

Abstract: Hydrogen sulfide (H2S) is an essential biological signaling molecule in diverse biological regulatory pathways. To provide new chemical tools for H2S imaging, we report here a fluorescent H2S detection platform (HSN2-BG) that is compatible with subcellular localization SNAP-tag fusion protein methodologies and use appropriate fusion protein constructs to demonstrate mitochondrial and lysosomal localization. We also demonstrate the eӽcacy of this detection platform to image endogenous H2S in Chinese hamster ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…16G) and a related compound AP123 combine the well-known mitochondrial targeting moiety triphenylphosphonium (TPP + ) with a dithiolethione H 2 S delivery moiety. AP39 and AP123, as expected, selectively increase the H 2 S signal in the mitochondrial compartment of cultured cells (Le Szczesny et al, 2014;Montoya and Pluth, 2016) and exert cytoprotective effects in various cell types (e.g., endothelial cells, epithelial cells, platelets, neurons, cardiac myocytes) against various forms of oxidative stress (H 2 O 2 , rotenone, glucose oxidase, elevated extracellular glucose, anoxia/reoxygenation) in vitro in high nanomolar/low micromolar concentrations (D'Araio et al, 2014Le Trionnaire et al, 2014Szczesny et al, 2014;Emerson et al, 2015;Sitek et al, 2015;Ahmad et al, 2016a;Chatzianastasiou et al, 2016;Ger} o et al, 2016;Zhao et al, 2016a;Lobb et al, 2017). Currently, AP39, which appears to be a more effective H 2 S releaser than AP123 (Gerö et al, 2016), has been studied more extensively.…”
Section: Mitochondrially Targeted H 2 S Donorssupporting
confidence: 69%
See 2 more Smart Citations
“…16G) and a related compound AP123 combine the well-known mitochondrial targeting moiety triphenylphosphonium (TPP + ) with a dithiolethione H 2 S delivery moiety. AP39 and AP123, as expected, selectively increase the H 2 S signal in the mitochondrial compartment of cultured cells (Le Szczesny et al, 2014;Montoya and Pluth, 2016) and exert cytoprotective effects in various cell types (e.g., endothelial cells, epithelial cells, platelets, neurons, cardiac myocytes) against various forms of oxidative stress (H 2 O 2 , rotenone, glucose oxidase, elevated extracellular glucose, anoxia/reoxygenation) in vitro in high nanomolar/low micromolar concentrations (D'Araio et al, 2014Le Trionnaire et al, 2014Szczesny et al, 2014;Emerson et al, 2015;Sitek et al, 2015;Ahmad et al, 2016a;Chatzianastasiou et al, 2016;Ger} o et al, 2016;Zhao et al, 2016a;Lobb et al, 2017). Currently, AP39, which appears to be a more effective H 2 S releaser than AP123 (Gerö et al, 2016), has been studied more extensively.…”
Section: Mitochondrially Targeted H 2 S Donorssupporting
confidence: 69%
“…It has been, therefore, assumed that these compounds either release their H 2 S "load" extracellularly (and then H 2 S diffuses into the cells and distributes into all cellular compartments), and/or the compounds themselves enter the cells (and, once again, enter all compartments without any particular targeting or specificity). Whether this was indeed the case, however, has not been directly tested until recently, when Montoya and Pluth (2016) produced a series of organelle-specific H 2 S detection probes using the SNAP-tag fusion protein methodology and tested subcellular localization of H 2 S after cells were exposed to various H 2 S donors. Indeed, NaHS, DATS, and GYY4137 produced an increase in all cellular compartments studied, including the mitochondria and the lysosomes.…”
Section: Mitochondrially Targeted H 2 S Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Pluth designed an organelle-targeted uorescent probe for detecting differential subcellular donation of H 2 S by incorporating SNAP-tag (benzylguanine-ligated substrates in combination with AGT fusion proteins to cause subcellular localization ability) into naphthalimide dye. 76 In addition to imaging endogenous H 2 S in Chinese hamster ovary cells, probe 57 was also applied to investigating the subcellular H 2 S distributions supplied by various H 2 S donors such as ADT-OH, dia-llyltrisulde (DATS), AP39 and GYY4137. A recent study has shown that H 2 S was overexpressed in cancer cells compared to normal cells due to the higher level of H 2 S related synthetases CBS and CSE in cancer cells.…”
Section: Azide Reductionmentioning
confidence: 99%
“…In an in vitro imaging study,A P39, an efficient H 2 S releasing agent in mitochondria, [21] was applied to mimic en-dogenousH 2 Si nstead of exogenous Na 2 Sw hich could be rapidly cleared by the cells. [22] As AP39 is membrane permeable and susceptible to intracellular esterase-catalyzed hydrolysis for H 2 Sr eleasing, H 2 Sc ould accumulate in cells. [23] HeLa cells were treated with probe (2 mm)a lone, or ac ombination of probe andA P39 (0.5 mm)a nd/orH 2 O 2 (50 mm).…”
mentioning
confidence: 99%